Bimbingan dan Konseling Pendekatan Rasional Emotif Perilaku untuk Mereduksi Kecemasan Akademik Remaja - M Amirullah; Yessika Nurmasari; Dini Permatasari; Widi Rizka Retnaningrum (Indonesian Journal of School Counseling: Theory, Application, and Development, 2022)
Academic anxiety is a condition of tension and worry which is a manifestation of wrong thoughts and feelings in a person which results in the inability to carry out and complete learning processes properly. Academic anxiety will cause disturbances in the thoughts, emotions and behavior of students. Some students take extra lessons to reduce academic anxiety, but other students who are not financially able will experience high academic anxiety. School counselors need to provide services to reduce academic anxiety, namely counseling services with a rational emotive behavior approach (REBT). The REBT approach views the aspects of thoughts, emotions and behavior as related components and the irrational beliefs that individuals have will have an impact on these three aspects. Irrational beliefs in students with academic anxiety need to be identified and debated.